NAVIGATION OF IMAGE IN THE MIDST OF BOYCOTT: MARKETING COMMUNICATION STRATEGIES OF COMPANIES IN RESPONDING TO ISRAELI PRODUCT ISSUES - Sazali, Hasan; Matondang, Abdul Rahman; Amal, Bakhrul Khair; Muhammadi, Qasem (JURNAL AL-IJTIMAIYYAH, 2024)
This research aims to analyze in depth the marketing communication strategies implemented by KFC, Starbucks, Unilever, and Pizza Hut in facing the boycott of Israeli products. Using a qualitative approach, semi-structured interviews were conducted with managers and marketing staff from company branches in North Sumatra. The data collected was analyzed using Nvivo software, which identified key themes related to determining marketing objectives, segmentation and targeting, as well as differentiation and positioning. The research results show that these companies are able to reduce the negative impact of boycotts by implementing strategies that focus on local adaptation, image strengthening and product innovation. This strategy has proven effective in maintaining consumer loyalty, maintaining market share, and strengthening their position in the global market. These findings emphasize the importance of flexibility, innovation and responsiveness in responding to sensitive global issues.